Satisfaction SATISFACTION OF MI DARUL ULUM TAMBAKREJO WARU SIDOARJO TEACHERS: THE ROLE OF WORK ENVIRONMENT AND SCHOOL COMPENSATION - Fachruddin, Arrozi; Didit Darmawan; Belouadah Ahmed Seif Eddine (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to analyze the effect of work environment and compensation on teacher satisfaction at MI Darul Ulum Tambakrejo Waru SidoarjoThis study uses a quantitative approach involving 32 teachers as respondents taken by census from MI Darul Ulum Tambakrejo Waru Sidoarjo. Data were collected through a questionnaire designed to measure teachers' perceptions of their work environment, compensation and satisfaction. The results of regression analysis show that work environment and compensation significantly affect teacher satisfaction. The work environment, which includes physical, social and psychological aspects, has a direct impact on teacher satisfaction. In addition, fair and comprehensive compensation also plays an important role in teachers' contribution. This study contributes to an in-depth understanding of the complex dynamics between work environment, compensation and teacher satisfaction. The implications of the results of this study can be used as a basis for the development of school policies that support the welfare and professionalism of teachers, especially in the Islamic education environment